Chlorine-free compound electrolyte for improving performance of magnesium battery and preparation method of chlorine-free compound electrolyte
By using a chlorine-free compound electrolyte, the specific components are mixed solutions of sodium sulfate, sodium carbonate and 2-methylimidazole, the problems of corrosion and low discharge voltage in magnesium air batteries are solved, and efficient discharge voltage and anode utilization efficiency are achieved.
Patent Information
- Application Number
- CN202510059357.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The pure magnesium anode material reacts with H+ in the electrolyte during the discharge process, resulting in severe corrosion, reducing the utilization efficiency and discharge voltage of the magnesium air battery.
A chlorine-free compound electrolyte is used, with a mixed solution of sodium sulfate, sodium carbonate and 2-methylimidazole. By adjusting its concentration and pH value, an electrolyte that improves the performance of magnesium batteries is formed.
The discharge voltage and anode utilization efficiency of magnesium air batteries have been significantly improved. The discharge voltage has been increased from -1.46V to -1.9V, the anode utilization efficiency has been increased to 87%, and the potential stability has been improved, and no large fluctuations in the potential are caused.
Smart Images

Figure CN119581755A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium-air battery electrolytes, and in particular relates to a chlorine-free composite electrolyte for improving the performance of a magnesium battery and a preparation method thereof. Background Art
[0002] At present, the shortage of fossil energy has become a serious problem faced by countries around the world. Magnesium-air batteries have obvious advantages over other air batteries. Although lithium-air batteries can be charged and discharged, they are prone to safety problems during use. At the same time, the cost of lithium is high and the theoretical specific capacitance is low. Although zinc-air batteries are safe and low in cost, the activity of zinc metal is poor and it is difficult to maintain a high output voltage. During the discharge process, a stable passivation film is formed on the surface of the aluminum electrode of the aluminum-air battery. This passivation film affects the continuous discharge process of the substrate, thereby increasing the potential of the aluminum electrode, resulting in a continuous decrease in the output voltage and power of the air battery. Compared with other air batteries, magnesium-air batteries have unique advantages. Magnesium metal has high electronegativity and high chemical activity. Magnesium has high theoretical capacity and voltage, is easy to process and prepare, and is safe during use. Therefore, magnesium-air batteries have become a new favorite of scientific researchers. Magnesium-air batteries can be used in many fields such as submarines, remote electronic communication equipment, and emergency rescue in the wild. But at the same time, magnesium-air batteries also have their own problems. Since the magnesium anode and the electrolyte need to be in constant contact during the discharge process, the magnesium anode and the H in the electrolyte are in contact with each other. + The cathode hydrogen evolution reaction occurs, generating insoluble discharge products such as Mg(OH)2 and other substances. The insoluble discharge products will cover the surface of the magnesium anode, hindering the continuous contact between the anode and the electrolyte, thus affecting the stability of the output voltage and output power. In addition, the cathode hydrogen evolution reaction will cause excessive corrosion of magnesium during the discharge process. The discharge products formed by excessive corrosion will contain some undissolved magnesium matrix. These magnesium matrices will enter the electrolyte and dissolve without participating in the actual discharge charge transfer process, greatly reducing the anode utilization efficiency and specific capacitance, and shortening the service life of the magnesium-air battery.
[0003] At present, the two solutions to improve the discharge performance of magnesium-air batteries are mainly to treat the anode material and adjust the chemical composition of the magnesium-air battery electrolyte. Generally speaking, the methods for treating the anode material include alloying or heat treatment. The alloying treatment is used, such as adding tin, calcium and other elements to inhibit the influence of impurity elements such as iron and manganese on the magnesium matrix, reducing the potential difference between the matrix and the second phase to improve the corrosion resistance of magnesium during the discharge process. Heat treatment schemes such as low-temperature tempering treatment and improving the content and distribution of the second phase in the alloy can promote the uniform dissolution of the anode during the discharge process and improve the discharge performance. But in general, the method of using alloying or heat treatment methods to improve the discharge performance of air batteries requires expensive processing equipment and is too time-consuming. Although such methods improve the discharge performance of the anode, the effect of improving the discharge performance is not obvious. Compared with the scheme of improving the anode, the scheme of adjusting the composition of the magnesium-air battery electrolyte is simple to operate, low-cost, green and efficient, and can significantly inhibit corrosion during the discharge process to achieve a comprehensive improvement in the discharge voltage and anode utilization efficiency. Therefore, the scheme of adjusting the actual chemical composition of the magnesium-air battery electrolyte is of great significance for promoting the actual production and application of magnesium-air batteries.
[0004] At the current stage, there are few inventions for improving the discharge performance of air batteries by adjusting the chemical composition of magnesium-air battery electrolytes, which deserves in-depth study. The patent application number CN118610664A, "An electrolyte containing sodium dihydrogen phosphate additive and its application in magnesium-air batteries", proposes a mixture of disodium hydrogen phosphate and sodium acetate as a magnesium-air battery electrolyte. The invention shows the discharge voltage under three current densities. The invention shows that the anode has the highest discharge voltage in 0.005 mol / L sodium acetate and 0.5 mol / L sodium acetate, but its anode discharge voltage is not stable. At the same time, the invention shows that the absolute value of the discharge voltage of the magnesium anode during the discharge process in the electrolyte is too low, only around 1.6V, which cannot meet the actual use of the air battery. At the same time, the patent does not show the discharge performance of the magnesium anode under a small current state. The discharge performance under a small current density is of great significance to magnesium-air batteries, because magnesium-air batteries are mostly used in remote electronic devices, and the current density used in this case is very low, about 0.4-0.6mA·cm -2 .
[0005] The patent application number CN118472433A, "A method for preparing a 3-pyridinesulfonic acid magnesium air battery electrolyte", proposes an electrolyte composed of 0.01 mol / L corrosion inhibitor gadolinium chloride, 0.1 mol / L titanium iron reagent, and 0.6 mol / L sodium chloride to improve the performance of magnesium air batteries. This method can improve the corrosion resistance of magnesium alloys in solution. After compounding, it can reduce the excessive consumption of the magnesium matrix when the complexing agent titanium iron reagent is used alone. However, the addition of corrosion inhibitors reduces the anode dissolution rate, which is very unfavorable for improving discharge activity. The maximum discharge voltage is only 1.557V. At the same time, the addition of chlorine will definitely promote corrosion and reduce the utilization efficiency of the matrix. The results show that the electrolyte did not significantly improve the anode utilization efficiency. The anode utilization efficiency was only increased to 52.8%, which is far from meeting the actual engineering requirements. In addition, the current density used in the test of this patent is too high, which is 5mA·cm -2 , without considering the battery performance under low current density conditions. Summary of the invention
[0006] The present invention aims at the pure magnesium anode material due to the reaction with H in the electrolyte. + The reaction causes serious corrosion, which greatly reduces the utilization efficiency; the insoluble Mg(OH)2 is deposited on the anode surface, resulting in low discharge voltage and large fluctuations. The present invention provides a chlorine-free composite electrolyte for improving the performance of magnesium batteries and a preparation method thereof.
[0007] The invention provides a chlorine-free composite electrolyte for improving the performance of a magnesium battery, specifically a mixed solution of sodium sulfate, sodium carbonate, 2-methylimidazole and deionized water.
[0008] Furthermore, the concentration of sodium sulfate in the electrolyte is 0.45-0.65 mol / L, the concentration of 2-methylimidazole is 0.0005-0.006 mol / L, the concentration of sodium carbonate is 0.0005-0.025 mol / L, and the pH is 7.0±0.2.
[0009] The present invention provides a method for preparing the chlorine-free composite electrolyte for improving the performance of a magnesium battery, and the specific steps are as follows:
[0010] (1) mixing sodium sulfate, sodium carbonate and 2-methylimidazole to prepare a mixed material;
[0011] (2) adding deionized water to the mixed material, and then accelerating the stirring of the mixed material and liquid to form a uniform transparent solution;
[0012] (3) Using sodium hydroxide or dilute sulfuric acid to adjust the pH value of the solution obtained in step (2) to obtain the chlorine-free composite electrolyte for improving the performance of the magnesium battery.
[0013] Furthermore, in the step (2), a drainage device consisting of a funnel and a 500 mL beaker is used to introduce deionized water into the mixed material placed in the container, and the mixed liquid is slowly poured along the inner wall of the container while stirring.
[0014] Furthermore, in step (2), the stirring speed is 100-150 rpm.
[0015] Furthermore, in the step (2), the heating state needs to be maintained during the stirring process, and the heating temperature is 40-50°C.
[0016] Furthermore, in the step (3), the pH value of the prepared electrolyte is regulated by a pH-conductivity meter, and the pH value = 7.0±0.2.
[0017] The present invention also provides an application method of the chlorine-free composite electrolyte for improving the performance of magnesium batteries, specifically:
[0018] An external current is applied to the electrochemical workstation and the battery voltage change signal is collected. Pure magnesium is used as the anode material, and 15%-25% of the surface area of the magnesium anode material is exposed in a chlorine-free composite electrolyte that improves the performance of the magnesium battery.
[0019] Furthermore, in the use method, the specific pure magnesium material of the magnesium anode has a tin content of 0.01wt.%-0.012wt.%, and an iron / manganese impurity content of less than 0.01wt.%.
[0020] Furthermore, in the method of use, the current density of the current is 0.3-3 mA·cm -2 .
[0021] Furthermore, in the method of use, the positive electrode material includes copper sheet, graphite powder and platinum mesh; and the air cathode is prepared by 500MPa pressing and shearing treatment.
[0022] Beneficial effects of the present invention:
[0023] The chlorine-free composite electrolyte for improving the performance of magnesium batteries provided by the present invention uses sodium sulfate instead of sodium chloride to avoid the continuous corrosion of chloride ions on the magnesium matrix, uses sodium carbonate and 2-methylimidazole as additives, and adjusts the ratio of the two to achieve a significant improvement in the discharge voltage and anode utilization efficiency of magnesium-air batteries for the first time, and utilizes the reaction of sodium carbonate with the magnesium matrix to form a thin magnesium carbonate layer. This layer reduces the H in the solution. +Continuous contact with the magnesium matrix avoids the formation of a thick Mg(OH)2 layer. On the other hand, the large π-bond electronegative group formed by the benzene ring-like structure in the 2-methylimidazole molecule is attracted to the positively charged magnesium matrix to further compact the surface film layer, thereby further ensuring that the discharge product film layer is thin and dense. The chlorine-free composite electrolyte for improving the performance of magnesium batteries prepared by the present invention achieves simultaneous improvement in utilization efficiency and discharge voltage.
[0024] After the pure magnesium is discharged in the chlorine-free composite electrolyte for improving the performance of the magnesium battery provided by the present invention, the discharge voltage is increased from -1.46V to -1.9V (close to the theoretical value), which is a significant increase of about 440mV, indicating that the chlorine-free composite electrolyte for improving the performance of the magnesium battery significantly increases the discharge voltage of the air battery. At the same time, the potential is stable during the discharge process, and there is no large fluctuation in the potential.
[0025] The chlorine-free composite electrolyte for improving the performance of magnesium batteries provided by the present invention greatly improves the utilization efficiency of magnesium anode to 87%. The specific capacitance is greatly improved, which is about 749.2 mAh·g compared with NaCl solution. -1 .
[0026] The chlorine-free composite electrolyte for improving the performance of magnesium batteries provided by the present invention successfully and significantly improves the discharge performance of air batteries, not only ensuring a high discharge voltage, which is close to the theoretical voltage of magnesium air batteries of 2.37V, but also achieving a high utilization efficiency of 87%, thus having great application potential.
[0027] The present invention prepares a chlorine-free composite electrolyte for improving the performance of magnesium batteries. Compared with the previous inventions, it has the following advantages: sodium sulfate is used to replace sodium chloride to avoid the corrosion and dissolution problem of magnesium during discharge caused by unfavorable ions such as chlorine. At the same time, the precipitation film formation principle of the reaction between sodium carbonate and magnesium matrix and the chemical adsorption principle of 2-methylimidazole and magnesium anode are used to effectively avoid the formation of a loose and thick discharge product layer. The combination of the three meets the application of magnesium-air batteries under low current density conditions. The chlorine-free composite electrolyte for improving the performance of magnesium batteries is green and efficient, easy to configure, low-cost, and convenient and fast. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The molecular structure and atomic electronegativity diagram of 2-methylimidazole;
[0029] Figure 2 The impedance analysis diagram of the pure magnesium anode after immersion for 24 hours in the comparative example and the embodiment of the present invention;
[0030] Figure 3The figures are the potentiodynamic polarization diagrams of the pure magnesium anode after immersion for 1, 24, 48 and 72 hours in the comparative example and the embodiment of the present invention; wherein, Figure (a) is the potentiodynamic polarization diagram of the pure magnesium anode in the comparative example 1; Figure (b) is the potentiodynamic polarization diagram of the pure magnesium anode in the embodiment 1; Figure (c) is the potentiodynamic polarization diagram of the pure magnesium anode in the embodiment 2; Figure (d) is the potentiodynamic polarization diagram of the pure magnesium anode in the embodiment 3;
[0031] Figure 4 The hydrogen evolution diagram of the pure magnesium anode after immersion for 7 days in the comparative example and the embodiment of the present invention;
[0032] Figure 5 The graphs are weight loss and pH change of pure magnesium anode after immersion for 7 days in the comparative example and the embodiments of the present invention; wherein, Figure (a) is a weight loss change graph of the comparative example and embodiments 1-3, and Figure (b) is a pH change graph of the comparative example and embodiments 1-3;
[0033] Figure 6 The discharge voltage curves of the pure magnesium anode at different current densities for 10 h in the comparative example and the embodiment of the present invention are shown in Figure (a) when the current density is 0.5 mA·cm -2 The discharge voltage curve of the discharge under 10h, Figure (b) is 2.5mA·cm -2 Discharge voltage curve of 10h discharge under the condition of ;
[0034] Figure 7 For pure magnesium anode, 0.5 mA·cm -2 Surface and cross-sectional morphology after 10 h of discharge at a current density of 0.5 mA·cm -2 Surface morphology after discharge at current density of 0.5 mA cm-1 for 10 h; Figure (b) shows the surface morphology of the pure magnesium anode at 0.5 mA cm-1 in Example 1. -2 Surface morphology after discharge at current density of 0.5 mA cm in Example 2. -2 Surface morphology after discharge at current density of 0.5 mA cm-1 for 10 h; Figure (d) shows the surface morphology of the pure magnesium anode at 0.5 mA cm-1 in Example 3. -2 Surface morphology after discharge at current density of 0.5 mA cm-1 for 10 h; Figure (e) shows the surface morphology of the pure magnesium anode at 0.5 mA cm-1 in Comparative Example 1. -2 Cross-sectional morphology after discharge at current density of 0.5 mA·cm in Example 1; Figure (f) is a cross-sectional morphology of a pure magnesium anode after discharge at current density of 0.5 mA·cm in Example 1 -2 Cross-sectional morphology after discharge at current density of 0.5 mA·cm in Example 2; Figure (g) is a cross-sectional morphology of a pure magnesium anode after discharge at current density of 0.5 mA·cm in Example 2 -2 Cross-sectional morphology after discharge at current density of 10 h; Figure (h) is a 0.5 mA·cm -2Cross-sectional morphology after discharge for 10 h at the current density. DETAILED DESCRIPTION
[0035] The following is further explained by the embodiments provided by the present invention. It is hereby pointed out that the following embodiments only illustrate the implementation method of the present invention. Those skilled in the art can make non-essential and appropriate improvements to the implementation method after skilled operation, and the implementation method is not limited to the embodiments provided by the present invention.
[0036] The chlorine-free composite electrolytes for improving the performance of magnesium batteries prepared in Comparative Example 1 and Examples 1-9 were tested under the following conditions, respectively, and the results obtained were plotted in graphs and tables.
[0037] Pure magnesium is used as the anode of the air battery, and the electrolyte is the electrolyte prepared in Comparative Example 1 and Examples 1-9; the magnesium anode material is energized using a Princeton electrochemical workstation; the specific composition of the pure magnesium anode includes ≥99.9wt.% magnesium, 0.01wt.%-0.012wt.% tin, and ≤0.1wt.% impurity elements such as manganese and iron. The applied current density is 0.5mA·cm -2 and 2.5 mA cm -2 The cathode material is prepared by 500MPa pressure treatment, shearing and other methods, and is composed of copper mesh, platinum sheet and graphite powder.
[0038] Before the experiment, the anode sample needs to be polished with sandpaper until the particle size is 2000. After polishing, spray alcohol and blow dry, and cool to room temperature. The pure magnesium anode material is placed in Example 1 for about 24 hours, and the area exposed to the electrolyte in the impedance analysis test is about 1.5cm 2 , set the test frequency to 10 -2 ~10 5 Hz, and the material impedance analysis diagram was obtained; the pure magnesium anode material was placed in the electrolyte for 1-72h, and the area exposed to the electrolyte in the potentiodynamic polarization test was about 1.5cm 2 The scanning rate of the potentiodynamic polarization test was 1 mV S -1 The anodic scan starts at the open circuit potential until the current density reaches 10 mA cm -2 The cathode scan starts at 300 mV below the open circuit potential and ends when the current density reaches 10 mA cm -2; Obtain a potentiodynamic polarization diagram of pure magnesium anode material in electrolyte; Leave the pure magnesium anode material to stand at room temperature for seven days as in Example 1, calculate the weight loss before and after, and record the amount of hydrogen released during the immersion process and the pH change of the comparative example. The size of the pure magnesium anode material used at this time is 10×10×3mm, and obtain a seven-day hydrogen evolution change diagram, a weight loss diagram, and a pH change diagram. After the discharge is completed, observe the surface and cross-sectional morphology of the pure magnesium anode after 10 hours of discharge in Example 1, and obtain the surface and cross-sectional morphology diagrams after discharge. The discharge current density is 0.5mA·cm -2 and 2.5 mA cm -2 The discharge test duration is 10 hours; the weight loss of the pure magnesium anode material after discharge in the comparative example is recorded to obtain the anode utilization efficiency and discharge specific capacitance table.
[0039] Comparative Example 1
[0040] Deionized water was added to sodium chloride and stirred using a 45 mm rotor at a stirring speed of 120 rpm. The solution was monitored using a pH-conductivity meter until the pH value reached 7.0±0.2. A comparative electrolyte was prepared. The concentration of the comparative electrolyte was 0.6 mol / L.
[0041] The impedance analysis after 24 hours of immersion is shown in the figure below. Figure 2 As shown in the figure, the pure magnesium anode shows a small capacitive arc in Comparative Example 1, and an inductive arc appears in the 24h impedance diagram, which means that the pure magnesium anode has poor corrosion resistance in the comparative example, indicating that it dissolves faster during the discharge process, which is not conducive to improving the anode utilization efficiency. Figure 3 As shown, the anode polarization curve of pure magnesium anode is continuously delayed to the right as the immersion time increases, which means that the corrosion rate of pure magnesium anode is continuously accelerated in comparative example 1, indicating that its microgalvanic corrosion is serious, which may cause a large amount of discharge products to accumulate and is not conducive to the continuous discharge process; Figure 4 This indicates that the pure magnesium anode has the fastest hydrogen evolution rate during the 7-day immersion test, reaching 4.3 mL cm -2 , reflecting that its corrosion and dissolution problems are serious. Figure 5 This indicates that the weight loss rate is 1.75 mg cm -2 ·d -1 At the same time, the pH value increased rapidly, reaching 10.3 after 7 days, indicating that the anode and the comparative example 1 + The reaction is more, resulting in a significant increase in the alkalinity of Comparative Example 1. In Comparative Example 1, the anode discharge voltage is as follows Figure 6 As shown, pure magnesium anode at 0.5 mA cm -2The discharge voltage is only 1.46V under the current density. As the current density increases, the voltage decreases more significantly, only 1.4V. This shows that Comparative Example 1 cannot provide a good output voltage for the pure magnesium anode, which is not conducive to improving the discharge performance. Table 1 shows the utilization efficiency and specific capacitance changes of the pure magnesium anode after discharge in Comparative Example 1. The low utilization efficiency and specific capacitance indicate that the pure magnesium anode has poor discharge performance in Comparative Example 1.
[0042] The calculation formula of anode utilization efficiency is as follows:
[0043]
[0044] The specific capacitance is calculated as follows:
[0045]
[0046] The theoretical weight loss calculation formula is as follows:
[0047]
[0048] The actual weight loss calculation formula is as follows:
[0049] ΔW=ΔW theo +ΔW self-corr +ΔW chunk effect (4)
[0050] From formula (1-4), we can see that the actual utilization efficiency depends on the self-corrosion weight loss (ΔW self-corr ) and the amount of undissolved magnesium matrix encapsulated in the discharge products (ΔW chunk effect ), and the theoretical weight loss (ΔW theo ) is irrelevant. The weight loss from self-corrosion has been Figure 4 Reaction, the pure magnesium anode has the fastest hydrogen evolution rate in Comparative Example 1, and the mass of the magnesium matrix consumed by self-corrosion is the largest. Figure 7 The figure shows the content of discharge products on the surface and in the cross section of the pure magnesium anode after 10 hours of discharge. It was observed that a large amount of discharge products were deposited on the surface of the anode after discharge in Comparative Example 1, which significantly reduced the contact area between the anode and the electrolyte and was not conducive to increasing the discharge voltage, explaining the reason for the low discharge voltage of the anode in Comparative Example 1; at the same time, the cross-sectional view of the discharge product shows that after discharge in Comparative Example 1, there are many undissolved magnesium matrices, which are dissolved in the solution without participating in charge transfer, greatly reducing the utilization efficiency and specific capacitance of the anode. In summary, the discharge voltage, utilization efficiency and specific capacitance of the pure magnesium anode in Comparative Example 1 were not improved.
[0051] Example 1
[0052] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.45 mol / L, the concentration of 2-methylimidazole is 0.001 mol / L, and the concentration of sodium carbonate is 0.001 mol / L;
[0053] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0054] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the mixture was heated while stirring at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and the chlorine-free composite electrolyte for improving the performance of the magnesium battery described in Example 1 was prepared;
[0055] like Figure 2 As shown in FIG. 1 , the capacitive reactance arc of the pure magnesium anode material in Example 1 is large, and there are two obvious capacitive reactance arcs, indicating that the corrosion resistance of the anode is improved. This proves that compared with Comparative Example 1, the pure magnesium anode material in Example 1 has a larger charge transfer resistance and better corrosion resistance; the potentiodynamic polarization diagram of the pure magnesium anode material in Example 1 is shown in FIG. Figure 3 As shown in (b), the 24h anodic polarization curve shows a pseudo-passivation phenomenon, which indicates that the corrosion dissolution of the anode is inhibited and the corrosion resistance is improved. Figure 4 and Figure 5 The hydrogen evolution, weight loss and pH changes of the pure magnesium anode material in Example 1 during the 7-day immersion process are shown. The hydrogen evolution of the pure magnesium anode in Example 1 is less than that in Comparative Example 1, which is 3.9 mL cm -2 At the same time, the weight loss and pH change were also lower than those in Comparative Example 1, which were 0.47 mg·cm -2 ·d -1 and 10.2. This shows that H + The reaction with the magnesium matrix is suppressed, and Example 1 helps to suppress the self-corrosion process of the magnesium anode. It should be pointed out that the three materials provided by the present invention have similar pH values after being dissolved in water, and will not cause large changes in pH and affect each other. Figure 1 The chemical structure of 2-methylimidazole and the electronegativity of each atom are shown. The benzene ring structure of 2-methylimidazole can form a large π bond with a negatively charged group. The first-principle calculation found that the electronegativity of the nitrogen atom on the benzene ring is -0.508, which can attract the positively charged magnesium matrix and cover it, thereby improving the corrosion resistance of magnesium. At the same time, the reaction equation of sodium carbonate and magnesium is 2NaCO3+Mg 2+ →MgCO3+2Na +It is known that MgCO3 is easier to deposit on the anode surface than Mg(OH)2, and the density of MgCO3 is significantly higher than that of loose Mg(OH)2, which helps to form a thin product layer to inhibit the deposition of loose corrosion products. In summary, sodium sulfate avoids the adverse effects of chloride ions, and the synergistic effect of 2-methylimidazole and sodium carbonate helps to form a thin, uniform and dense protective layer on the surface, inhibiting the H in the electrolyte. + This explains why Example 1 inhibits anode self-corrosion. Figure 6 As shown in Table 1, the discharge voltage of the pure magnesium anode material in Example 1 at two current densities is about 200 mV higher than that in Comparative Example 1, indicating that Example 1 effectively improves the discharge voltage. -2 At the current density, the utilization efficiency is increased by about 11.2%, and the specific capacitance is increased by about 249.2 mAh g -1 ; 2.5mA·cm -2 At the current density, the utilization efficiency is increased by about 10%, and the specific capacitance is increased by about 230mAh·g -1 , which shows that Example 1 effectively improves the discharge performance of pure magnesium anode materials in electrolyte. At the same time, the surface and cross-sectional morphology after discharge found that the overall discharge product layer became thinner, which shows that Example 1 does help to change the morphology of the discharge product layer, effectively reducing the deposition of discharge products during the discharge process, facilitating the continuous contact between the electrolyte and the pure magnesium anode material, and maintaining a high discharge voltage. At the same time, there is no obvious undissolved magnesium matrix, which shows that Example 1 also reduces the matrix consumption during the discharge process. Combined with Example 1, the self-corrosion behavior of the magnesium anode is suppressed, which explains why Example 1 improves the utilization efficiency and specific capacitance of the magnesium anode.
[0056] Example 2
[0057] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.45 mol / L, the concentration of 2-methylimidazole is 0.003 mol / L, and the concentration of sodium carbonate is 0.005 mol / L;
[0058] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0059] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was accompanied by heating at a temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value reached 7.0±0.2; Example 2 was prepared.
[0060] like Figure 2As shown in FIG. 1 , after immersion for 24 hours, the capacitive reactance arc of the pure magnesium anode material in Example 2 is significantly greater than that in Comparative Example 1, and no inductive reactance occurs, indicating that Example 2 improves the corrosion resistance of the anode material; the potentiodynamic polarization diagram of the pure magnesium anode material in Example 2 is shown in FIG. Figure 3 As shown in the figure, the anode polarization curve showed a passivation phenomenon at 48h, indicating that the dissolution process of the anode in Example 2 was inhibited, and Example 2 improved the anode corrosion resistance compared with Comparative Example 1. After seven days of immersion, the amount of hydrogen evolution and weight loss were 3.9mL·cm -2 and 0.33 mg cm -2 ·d -1 , pH changed to 10.2, which was lower than that of Comparative Example 1, which also proved that Example 2 effectively inhibited H + A large amount of self-corrosion and dissolution caused by reaction with the magnesium matrix. 0.5mA·cm -2 At the current density, after 10 hours of discharge, the absolute value of the discharge voltage of the pure magnesium anode reaches 1.8V, indicating that it increases the discharge voltage by about 300mV. Comparing the utilization efficiency and specific capacitance values shown in Table 1, it is found that Example 2 has a high capacitance at 0.5mA·cm -2 At the current density, the anode utilization efficiency and specific capacitance are effectively improved to 72.9% and 1650mA·h·g -1 As the current density increases, the battery performance can still be improved, 2.5mA·cm -2 At the current density, the utilization efficiency is increased by about 15%. The changes in these indicators show that Example 2 effectively improves the discharge performance of the pure magnesium anode and effectively increases the service life of the anode material. The cross-sectional morphology of the surface area of the pure magnesium anode after discharge is as follows Figure 7 As shown, it was observed that a dense film layer was formed on the surface after discharge, corresponding to high utilization efficiency and specific capacitance.
[0061] Example 3
[0062] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.5 mol / L, the concentration of 2-methylimidazole is 0.005 mol / L, and the concentration of sodium carbonate is 0.01 mol / L;
[0063] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0064] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was combined with heating at a temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 3 was prepared.
[0065] like Figure 2As shown in the figure, the capacitive reactance arc of the pure magnesium material in Example 3 is the largest after immersion for 24 hours, which proves that the anode material has the best corrosion resistance in Example 3. At the same time, after immersion for 96 hours, the anode polarization curve still shows obvious passivation phenomenon, which also shows that it is most helpful to inhibit the self-corrosion phenomenon of the magnesium matrix. Figure 4-5 As shown in Figure 3, the amount of hydrogen released by the pure magnesium material after immersion for seven days is 2.5 mL cm -2 The corresponding weight loss is only 0.26 mg cm -2 ·d -1 , pH increased to 9.9. This shows that Example 3 inhibits the interaction between the magnesium anode and H in the electrolyte. + The reaction capacity is the strongest and the restriction on the self-corrosion behavior of magnesium anode is the best. 0.5mA·cm -2 At the current density, the absolute value of the discharge voltage is increased to 1.9V. Compared with Comparative Example 1, it is increased by about 400mV. It is known that the theoretical voltage of the magnesium anode is 2.3V. The absolute value of the potential reached by the pure magnesium anode material in Example 3 is close to the theoretical value, indicating that Example 3 greatly improves the anode discharge performance. -2 Under the current density, Example 3 still significantly increases the discharge voltage by about 400 mV, which indicates that the discharge performance of the pure magnesium anode in Example 3 is stable and reliable. By observing the changes in utilization efficiency and specific capacitance value, it is found that the pure magnesium material in Example 3 is 0.5 mA·cm -2 The current density is 87% and the specific capacitance is 1960 mAh g -1 2.5mA·cm -2 At the current density, the utilization efficiency is still 80%, which fully meets the actual production and living needs. Example 3 significantly improves the discharge performance of the pure magnesium anode. The surface area cross-sectional morphology after discharge is as follows Figure 7 (d) and Figure 7 As shown in (h), it was observed that the pure magnesium anode material formed a dense, uniform and thin 2 μm thick discharge product layer after discharge in Example 3. This layer not only effectively suppressed the H + The unfavorable hydrogen evolution reaction with the magnesium matrix reduces the self-corrosion rate and improves the anode utilization efficiency, and avoids the formation of a thick discharge product layer that affects the charge transfer process, thereby greatly increasing the discharge voltage, which ultimately determines that the pure magnesium anode material exhibits excellent discharge performance in Example 3.
[0066] Example 4
[0067] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.5 mol / L, the concentration of 2-methylimidazole is 0.0045 mol / L, and the concentration of sodium carbonate is 0.015 mol / L;
[0068] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0069] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was combined with heating at a temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 4 was prepared.
[0070] like Figure 6 As shown in Table 1, 0.5 mA cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 4 was increased to 1.81 V. -2 At this current density, the discharge voltage is increased to 1.72 V, which is significantly higher than the voltage shown in Comparative Example 1. At the same time, the anode utilization efficiency and specific capacitance are also greatly improved, 0.5 mA cm -2 At the current density, they reached 84% and 1897.5 mAh g -1 ; When the current density increases, 2.5mA·cm -2 At the current density, they reached 70.6% and 1594.8 mAh g -1 The pure magnesium anode material in Example 4 exhibited good discharge performance.
[0071] Example 5
[0072] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.55 mol / L, the concentration of 2-methylimidazole is 0.0045 mol / L, and the concentration of sodium carbonate is 0.02 mol / L;
[0073] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0074] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the materials were heated while stirring at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 5 was prepared.
[0075] Figure 6 Table 1 summarizes the discharge performance of the magnesium anode in Example 5, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 5 was increased to 1.72 V. -2 At this current density, the discharge voltage increased to 1.68 V, which is significantly higher than the voltage shown in Comparative Example 1. At the same time, by comparing the anode utilization efficiency and specific capacitance value, it was found that 0.5 mA cm -2 At the current density, they reached 73.2% and 1653.6 mAh g -1; When the current density increases, 2.5mA·cm -2 At the current density, they reached 68.4% and 1545.1 mAh·g -1 The discharge performance of the pure magnesium anode material in Example 5 shows high discharge performance at various current densities.
[0076] Example 6
[0077] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.55 mol / L, the concentration of 2-methylimidazole is 0.005 mol / L, and the concentration of sodium carbonate is 0.02 mol / L;
[0078] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0079] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the materials were heated while stirring at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 6 was prepared.
[0080] The discharge performance of the magnesium anode in Example 6 is also higher than that in Comparative Example 1, 0.5 mA·cm -2 At the current density of 2.5 mA cm, the discharge voltage of the pure magnesium anode in Example 6 was increased to 1.7 V, which was about 240 mV higher than that in Comparative Example 1. -2 At this current density, the discharge voltage increased to 1.66 V. At the same time, it was found that 0.5 mA cm -2 At the current density, the anode utilization efficiency and specific capacitance reached 70.2% and 1585.8 mAh g respectively. -1 ; The current density increased to 2.5 mA cm -2 When the -1 .
[0081] Example 7
[0082] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.6 mol / L, the concentration of 2-methylimidazole is 0.0055 mol / L, and the concentration of sodium carbonate is 0.02 mol / L;
[0083] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0084] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the materials were heated while stirring at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 7 was prepared.
[0085] The discharge performance of the magnesium anode material in Example 7 is as follows: Figure 6 As shown in Table 1, 0.5 mA cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 7 was increased to 1.68 V. -2 At this current density, the discharge voltage is increased to 1.64 V, which is higher than the voltage shown in Comparative Example 1. At the same time, by comparing the anode utilization efficiency and specific capacitance value, it is found that 0.5 mA cm -2 At the current density, they reached 66.2% and 1495.4 mAh·g -1 ; 2.5mA·cm -2 At the current density, they reached 65.2% and 1472.8 mAh g -1 The pure magnesium anode material in Example 7 shows good discharge performance.
[0086] Example 8
[0087] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.6 mol / L, the concentration of 2-methylimidazole is 0.0055 mol / L, and the concentration of sodium carbonate is 0.025 mol / L;
[0088] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0089] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the materials were heated while stirring at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 8 was prepared.
[0090] Compared with Comparative Example 1, the discharge performance of the magnesium anode in Example 8 is improved, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 6 was increased to 1.66 V, which was about 200 mV higher than that in Comparative Example 1. -2 At this current density, the discharge voltage increased to 1.63 V. At the same time, it was found that 0.5 mA cm -2 At the current density, the anode utilization efficiency and specific capacitance reached 65.9% and 1488.7 mAh g respectively. -1 ; The current density increased to 2.5 mA cm -2 When the -1 .
[0091] Example 9
[0092] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, wherein the concentration of sodium sulfate is 0.65 mol / L, the concentration of 2-methylimidazole is 0.006 mol / L, and the concentration of sodium carbonate is 0.0025 mol / L;
[0093] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;
[0094] The uniformly mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the materials were heated while stirring at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; Example 9 was prepared.
[0095] The discharge performance of the magnesium anode in Example 9 is still better than that in Comparative Example 1, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 6 was increased to 1.65 V; at 2.5 mA·cm -2 At this current density, the discharge voltage increased to 1.63 V. At the same time, it was found that 0.5 mA cm -2 At the current density, the anode utilization efficiency and specific capacitance reached 62.2% and 1405 mAh g respectively. -1 ; The current density increased to 2.5 mA cm -2 When the -1 .
[0096] Table 1 Current density is 0.5 mA cm -2 The utilization efficiency and specific capacitance of pure magnesium anode in comparative examples and embodiments are shown in Table 2.
[0097] Utilization efficiency (%) <![CDATA[Specific capacitance (mAh·g -1 )]]> Comparative Example 1 53.6±1.2 1210.8±13.5 Example 1 64.8±3 1460±33.5 Example 2 72.9±1.4 1650.8±31.6 Example 3 87±1.7 1960±38.4 Example 4 84±1.7 1897.5±38.4 Example 5 73.2±1.5 1653.6±33.9 Example 6 70.2±1.3 1585.8±29.4 Example 7 66.2±1.5 1495.4±33.9 Example 8 65.9±0.7 1488.7±15.8 Example 9 62.2±0.5 1405±11.3
[0098] Table 2 Current density is 2.5 mA cm -2 The utilization efficiency and specific capacitance of pure magnesium anode in comparative examples and embodiments are shown in Table 2.
[0099]
[0100]
Claims
1. A chlorine-free composite electrolyte for improving the performance of magnesium batteries, characterized in that: The chlorine-free composite electrolyte for improving the performance of the magnesium battery is a mixed solution of sodium sulfate, sodium carbonate, 2-methylimidazole and deionized water.
2. The chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 1, characterized in that: The concentration of the sodium sulfate is 0.45-0.65 mol / L, the concentration of the 2-methylimidazole is 0.0005-0.006 mol / L, the concentration of the sodium carbonate is 0.0005-0.025 mol / L, and the pH is 7.0±0.
2.
3. The method for preparing the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 1, characterized in that: The following steps are involved: (1) Mixing sodium sulfate, sodium carbonate and 2-methylimidazole to prepare a mixed material; (2) adding deionized water to the mixed material, and then accelerating the stirring of the mixed material and liquid to form a uniform transparent solution; (3) Using sodium hydroxide or dilute sulfuric acid to adjust the pH value of the solution obtained in step (2) to obtain a chlorine-free composite electrolyte that improves the performance of the magnesium battery.
4. The method for preparing a chlorine-free composite electrolyte for improving the performance of a magnesium battery according to claim 3, characterized in that: In the step (2), deionized water is introduced into the mixed material placed in the container using a drainage device consisting of a funnel and a 500 mL beaker, and the mixed liquid is slowly poured along the inner wall of the container while stirring.
5. The method for preparing a chlorine-free composite electrolyte for improving the performance of a magnesium battery according to claim 3, characterized in that: In the step (2), the stirring speed is 100-150 rpm.
6. The method for preparing a chlorine-free composite electrolyte for improving the performance of a magnesium battery according to claim 3, characterized in that: In the step (2), the heating state needs to be maintained during the stirring process, and the heating temperature is 40-50°C.
7. The method for preparing a chlorine-free composite electrolyte for improving the performance of a magnesium battery according to claim 3, characterized in that: The pH value of the prepared electrolyte was regulated by a pH-conductivity meter, and the pH value was 7.0±0.
2.
8. The use of the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 1, characterized in that: The application method is: applying an external current to the electrochemical workstation and collecting the battery voltage change signal, pure magnesium is used as the anode material, and 15%-25% of the surface area of the magnesium anode material is exposed to the electrolyte that improves the discharge performance of the magnesium anode material.
9. The use of the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 8, characterized in that: In the application method, the specific pure magnesium material of the magnesium anode has a tin content of 0.01 wt.%-0.012 wt.%, and an iron / manganese impurity content of less than 0.01 wt.%.
10. The use of the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 8, characterized in that: In the application method, the current density of the current is 0.3-3 mA·cm -2 ; The positive electrode materials include copper sheet, graphite powder and platinum mesh; the air cathode is prepared by 500 MPa pressing and shearing treatment.
Citation Information
Patent Citations
Preparation method of 3-pyridine sulfonic acid magnesium air battery electrolyte
CN118472433A
Electrolyte containing sodium dihydrogen phosphate additive and application of electrolyte in magnesium air battery
CN118610664A
Magnesium air battery electrode, magnesium air battery, aromatic compound, and metal complex
CN108140920A
Electrolyte
CN114631216A
Magnesium battery compound electrolyte and preparation and use method thereof
CN115498329A